LITERATURE REVIEW: EFFECTIVENESS OF CARDIAC REHABILITATION IN PATIENTS WITH CORONARY HEART DISEASE - Ika Ainur Rofi'ah; Eka Nur So'emah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Background: Cardiac rehabilitation is an evidence-based intervention that includes physical exercise, health education, and modification of health behavior in patients with cardiovascular disease. Cardiac rehabilitation is considered as secondary prevention after acute coronary syndrome and improves treatment outcomes in patients with coronary heart disease. This literature review aimed to evaluate the effectiveness of cardiac rehabilitation in coronary heart disease patients. Methods: This present study was a literature review discussing cardiac rehabilitation for coronary heart disease patients. Results: The result showed that the functional capacity of the CR group was more increased compared to non-CR (p <0.001; α <0.05), left ventricular ejection fraction (LVEF) significantly increased in the CR group (p < 0.05; α <0.05), the medical cost of CR group was lower significantly (p=0.042; α <0.05), and the risk of recurrence rate was significantly lower in CR group (p=0.004; α <0.05). Conclusions: Cardiac rehabilitation is known to increase functional capacity, increase left ventricular ejection fraction (LVEF), reduce medical costs, and reduce the recurrence rate of patients with CHD.